2022
DOI: 10.3389/fnins.2022.917407
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Prefrontal Network With Pathway-Selective Manipulation in the Macaque Brain—A Review

Abstract: Macaque monkeys are prime animal models for studying the neural mechanisms of decision-making because of their close kinship with humans. Manipulation of neural activity during decision-making tasks is essential for approaching the causal relationship between the brain and its functions. Conventional manipulation methods used in macaque studies are coarse-grained, and have worked indiscriminately on mutually intertwined neural pathways. To systematically dissect neural circuits responsible for a variety of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Researchers have faced enormous challenges due to many obstacles, including limited transfection efficiency, inefficient light delivery and readout equipment, severe immune responses, and deficient injection protocols. After continuous improvement, NHP optogenetics has been transformed, fueled by developments in viral transudation efficiency (e.g., AAV2.1), surgical procedures (e.g., the convection-enhanced delivery (CED) method and window implantation), light delivery devices (e.g., the coaxial optrode), and readout approaches (e.g., fMRI and Ca 2+ imaging) [ 43 , 70 , 79 - 83 ]. In the last decade, primates optogenetics have started an era of mesoscopic neuronal circuit neuroanatomy and functional studies with cell-type specificity (e.g., dopamine neurons and Purkinje cells) and pathway selectivity (e.g., FEF to SC and LGN to V1).…”
Section: Genetic Tools Used For Neuronal Activity Manipulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have faced enormous challenges due to many obstacles, including limited transfection efficiency, inefficient light delivery and readout equipment, severe immune responses, and deficient injection protocols. After continuous improvement, NHP optogenetics has been transformed, fueled by developments in viral transudation efficiency (e.g., AAV2.1), surgical procedures (e.g., the convection-enhanced delivery (CED) method and window implantation), light delivery devices (e.g., the coaxial optrode), and readout approaches (e.g., fMRI and Ca 2+ imaging) [ 43 , 70 , 79 - 83 ]. In the last decade, primates optogenetics have started an era of mesoscopic neuronal circuit neuroanatomy and functional studies with cell-type specificity (e.g., dopamine neurons and Purkinje cells) and pathway selectivity (e.g., FEF to SC and LGN to V1).…”
Section: Genetic Tools Used For Neuronal Activity Manipulationmentioning
confidence: 99%
“…Such studies have focused on face gender discrimination, direction discrimination, decision confidence, value-based learning, working memory, reward prediction, visual perception, saccade movement, and forelimb movements. Most of those studies have been completed in the primary visual system and the frontal system [ 15 , 16 , 27 , 40 , 57 , 68 , 69 , 71 , 72 , 75 - 77 , 83 - 97 ] (Fig. 3 A).…”
Section: Genetic Tools Used For Neuronal Activity Manipulationmentioning
confidence: 99%
“…In this study, we used pathway-selective optogenetics ( 33 , 35 ) to selectively manipulate the axonal projections from the FEF to visual area MT to determine whether the FEF affects the attentional modulation of firing rates in MT via this direct pathway. In a previous study, we have shown that injection of a viral vector into the FEF leads to the incorporation of opsins into the axonal membrane of FEF neurons projecting to area MT ( 36 ).…”
mentioning
confidence: 99%